Trace element, Nd-Hf-Pb isotope geochemistry, and zircon U-Pb geochronology of the Baskil Dikes (Elazıg, Eastern Türkiye): Tracing Late Cretaceous continental arc magmatism in the Southern Neotethys - Sayit, Kaan; Ural, Melek; Koralay, Osman Ersin; Goncuoglu, Mehmet Cemal (Elsevier Gmbh, 2026)
During the Late Cretaceous, the dual subduction within the Southern Neotethyan domain resulted in the formation of an intra-oceanic arc complex (Y & uuml;ksekova Complex) as well as an Andean-type continental arc characterized by the Baskil Igneous Complex. The plutonic part of this continental arc is cut by numerous dikes, which are the main focus of this study. The dikes range in composition from basalt to dacite, while the host rocks are dacitic (granodioritic). All samples show negative Nb anomalies on the normal mid-ocean ridge basalt (N-MORB)-normalized plots. The samples can be grouped into five chemical types based on the level of depletion and the magnitude of Nb anomaly. Types 1 and 2 show a major contribution from a depleted mantle component, also supported by high epsilon Ndi and epsilon Hfi values in Type 2. Conversely, the other chemical types reflect a greater contribution from one or more enriched components, as indicated by their lower Zr/Nb and higher Nb/Yb ratios. All chemical types, with their relative Nb depletion, indicate slab-derived additions, which is strengthened by the Pb isotopic values of Type 2 samples plotting within the EM-2 field. On the other hand, the elevated Th and high Th/Nb ratios in Type 5 may imply assimilation of continental crust. The bulk geochemical characteristics of the studied dikes and host rocks imply their generation in a continental arc. The U-Pb zircon dating of the dikes and their granodioritic host rocks constrains their emplacement to a narrow interval, between 81 and 79 Ma. When the available geological and geochronological age data are taken into account, the intra-oceanic subduction and continental arc magmatism in the Southern Neotethys seem to have occurred simultaneously; the former created the Y & uuml;ksekova arc-basin system, whereas the latter generated the Baskil Arc.
Keywords: Continental arc; Dike; Southern Neotethys; U-Pb zircon dating; Isotope geochemistry